Foveal photoreceptors loss and then recovery after treatment in a chronic myelogenous leukemia patient. (17th August 2020) - Hsia, Ning-Yi; Lin, Chun-Ju; Lin, Hui-Ju; Wu, Kang-Hsi
Abstract: We report a 10-year-old boy with chronic myelogenous leukemia (CML)-related retinopathy of the eyes. Foveal photoreceptors loss was noted in the right eye, but it was restored with a continued ellipsoid zone after systemic 6-week imatinib mesylate and hydroxyurea treatment. Spectral-domain optical coherence tomography images of the foveal photoreceptors change in the right eye were taken. His best-corrected visual acuity of the right eye recovered from 20/100 to 20/20. Prompt treatment of the underlying CML could result in improvement or resolution of the ocular findings, and even foveal photoreceptors loss might be reversible with good visual acuity recovery.